Cofilin 2 Acts as an Inflammatory Linker Between Chronic Periodontitis and Alzheimer’s Disease in Amyloid Precursor Protein/Presenilin 1 Mice - Zeng, Qing; Fang, Qin; Zhou, Xincai; Yang, Hongfa; Dou, Yang; Zhang, Wenhao; Gong, Pu; Rong, Xianfang (Frontiers in Molecular Neuroscience, 2021)
Increasing evidence has shown a correlation between chronic periodontitis (CP) and Alzheimer’s disease (AD), which is the most common form of age-related dementia that affects a significant number of people without effective diagnosis and treatment. This study aimed to investigate potential protein links between CP and AD using an animal model. The hippocampus of CP model mice and controls were collected, and changes in protein expression were evaluated using two-dimensional differential in-gel electrophoresis (2D-DIGE) analysis combined with liquid chromatography tandem mass spectrometry. A total of 15 differentially expressed proteins were identified in CP model mice, as compared with the controls. Among them, five proteins, S100-A9, transthyretin, cofilin 2, peroxiredoxin 2, and lipocalin-2, were validated by Western blot according to their dual function both in inflammation and AD. Based on 2D-DIGE analysis, CP animal model had higher levels of S100-A9, cofilin 2, peroxiredoxin 2, and lipocalin-2 compared to controls. The level of cofilin2, one of the well-established proteins in the pathology of AD, was strongly correlated with the time course of CP pathology, indicating a specific molecular correlation between CP and AD. Moreover, to determine the role of cofilin 2 as the molecular link between CP and AD, neuroblastoma SK-N-SH APPwt cells were treated with 1 μg/ml of lipopolysaccharide from Porphyromonas gingivalis (P.g-LPS). The results showed the level of cofilin 2 increased significantly along with a prominent increase of the phosphorylation of protein phosphatase 2 (PP2A) and tau protein in the cell lysates of P.g-LPS-treated SK-N-SH APPwt cells. cofilin 2 inhibition resulted in a sharp decrease in PP2A dependent of tau phosphorylation. Furthermore, tumor growth factor (TGF)-β1 was one of the most important inflammatory cytokines for the Pg-LPS-induced cofilin 2 upregulation in SK-N-SH APPwt cells. These results showed that CP was associated with AD, whereas cofilin 2 could be a key link between the two diseases. Determining the association between CP and AD at the molecular mechanism will not only hold the direct evidence of the association between the two diseases but also provide a new way of preventing and treating AD.